KEANEKARAGAMAN JENIS GASTROPODA DI HUTAN MANGROVE SUNGAI KAKAP KABUPATEN KUBU RAYA - Rosario, Emanuel Luis; Anwari, M Sofwan; Rifanjani, Slamet; Darwati, Herlina (Universitas Tanjungpura, 2019)
Gastropod is one of the mollusk phylum that can adapt and decompose in mangrove forests. The mangrove forest in Sungai Kakap is an area that is slowly being opened due to the local community people’s activities. They opened land to build buildings, farms, and villages. This research is aimed at studying the diversity of Gastropod and the influence of the mangrove tree density on the gastropod diversity in the mangrove forest of Sungai Kakap, Sungai Kakap Village of Kubu Raya Regency. The data were taken in May 2018. The analysis was conducted using the observation method by making six observation lines. The lines were differentiated based on the density of the vegetations: dense, medium, and sparse. The number of Gastropods found in the Kakap River mangrove forest is 4 types of gastropods with a total of 252 individuals. Respectively from dense, medium, and sparse vegetation, the gastropod dominance index is 0.68, 0.37, and 0.51; the diversity index is 0.25, 0.49, and 0.33; the species average index is 0.27, 0.97, and 0.4; and the gastropod species richness index is 4.03, 1.18, and 0.7. Lastly, the species similarity index is respectively 86%, 66%, and 86%. Keywords: Gastropod, Mangrove Forests, Vegetation density.